Experimental study on the pressure drop oscillation characteristics of the flow boiling instability with FC-72 in parallel rectangle microchannels. (November 2019) - Lv, Yuanzheng; Xia, Guodong; Cheng, Lixin; Ma, Dandan
Abstract: Experiments of the pressure drop instability of flow boiling with FC-72 in 8 parallel rectangle microchannels with a hydraulic diameter of 88 μm were conducted in this study. The mass flux ranges from 578.2 to 2310.9 kg/m 2 s, the heat flux ranges from 0 to 1200 kW/m 2 and the measured pressure drop ranges from 13 to 275 kPa. The compressive volume in a nitrogen vessel before the test microchannels is set as 0, 5 and 15 ml in the experiments. The experimental results of heat transfer, pressure drop and the corresponding flow patterns are presented and analyzed. Furthermore, the critical vapour qualities at the onset of the flow boiling instability (OFBI) are predicted by a theoretical model considering the local pressure and the frictional pressure resistances. The calculated and experimental results indicate that the instable zones in a flow boiling stability map expand with increasing the compressive volume and decreasing the two types of resistances. The critical vapour quality at OFBI changes from 0.65 to 1 when the local pressure resistance combination coefficient is increased to 7.33 × 10 − 3 or the frictional pressure resistance combination coefficient is increased to 0.532. The physical mechanisms behind the phenomena are discussed according to the experimental results.